A survey on machine learning in mobile robotics - Cunha, João (2011)
Learning is a prerequisite for intelligent behavior. It is no surprise that Machine Learning, as one the most important fields of Artificial Intelligence, is becoming an increasingly hot-topic in Robotics. Machine Learning has several benefits, from enabling the use of historical data to improve future decisions, to solving problems that are difficult by hand-coding the solutions or to allow adptive behaviours in highly dynamic environments such as learning individual preferences in human-computer interaction environments. Recent advances in alghorithms and the increasing computational power avaiable at reduced size and weight, enabled the application of Machine Learning to the field of mobile robotics. This report presents an overview of the state of the art of the different applications of Machine Learning methodologies in mobile robotics.